The Role of Posyandu Cadres in the Management of Hypertension in Pudakpayung and Gedawang - Teddy Hardiansyah; Abrori; Iskim Luthfa (Jurnal Indonesia Sosial Sains, 2026)
The incidence of hypertension in the community has increased every year. The management of hypertension requires the optimization of the role of Posyandu cadres. This study aimed to describe the role of Posyandu cadres in the working area of the UPTD Puskesmas Pudakpayung in managing hypertension cases in the community. The regeneration of Posyanducadres has become one of the challenges addressed in this study. This study employed a descriptive quantitative design. The research was intended to provide an overview of the role of Posyandu cadres in hypertension management at a specific point in time without intervention. Data were collected using a questionnaire, with validity and reliability test results showing an r-value of 0.411 with a p-value of 0.05 and a Cronbach’s alpha of 0.965. Sampling was conducted using a total sampling technique. Data analysis was performed using univariate analysis. Based on statistical analysis, the roles of Posyandu cadres in the primary and secondary categories were more dominant than those in the tertiary category and were influenced by length of service and prior hypertension training history. Continuous empowerment is necessary to balance and strengthen the roles of Posyandu cadres in the primary, secondary, and tertiary categories.